Determination of eddy dissipation rate by Doppler lidar in Reykjavik, Iceland. (4th October 2020) - Yang, Shu; Petersen, Guðrún Nína; von Löwis, Sibylle; Preißler, Jana; Finger, David C.
Abstract: The temporal and spatial scale of atmospheric turbulence can be highly dynamic, requiring sophisticated methods for adequate detection and monitoring with high resolution. Doppler light detection and ranging (lidar) systems have been widely used to observe and monitor wind velocity and atmospheric turbulence profiles as Doppler lidar systems can provide continuous information about wind fields. The use of lidars in the subarctic region is particularly challenging as aerosol abundance can be very low, leading to weak backscatter signals. In the present study, we analysed data collected with a Leosphere Windcube 200S lidar system stationed in Reykjavik, Iceland, to estimate the eddy dissipation rate (EDR) as an indicator of turbulence intensity. For this purpose, we retrieved radial wind velocity observations from velocity–azimuth display scans and computed the EDR based on the Kolmogorov theory. We compared different noise filter thresholds, scan strategies and calculation approaches during typical Icelandic weather conditions to assess the accuracy and the uncertainty of our EDR estimations. The developed algorithm can process raw lidar observations, retrieve EDR and determine the qualitative distribution of the EDR. The processed lidar observations suggest that lidar observations can be of high importance for potential end‐users, for example air traffic controllers and aviation safety experts. The work is an essential step towards enhanced aviation safety in Iceland where aerosol concentration is in general low and severe turbulence occurs regularly. Abstract : Doppler lidars are widely employed around the world, especially in the wind energy and aviation sector, due to their ability to detect wind in the lower troposphere. We developed and applied an algorithm to estimate the eddy dissipation rate of atmospheric turbulence using lidar observations in Iceland, based on the Kolmogorov theory. This work has immediate implications for improving aviation safety as it will assist local air traffic controllers to monitor atmospheric turbulence and is applicable to other regions, especially at high latitudes.